Understanding how customers shape purchase decisions in the e-commerce marketplace - Indah Fatmawati; Abid Abiyyu Fathin; Pensri Jaroenwanit (Universitas Negeri Surabaya, Indonesia, 2023)
Consumer preferences for online purchases are increasing during the pandemic. This paper aims to understand how customers perceive their values regarding online shopping. Our study hypothesized that website design attractiveness, e-commerce marketplace reputation, and perceived ease of transaction are the predictors for customer-perceived value, influencing the online purchase decision. This study employs a survey with a total sample of 225 respondents of Indonesian marketplace consumers. Data is gathered through the distribution of Google-forms questionnaires and analyzed using the Structural Equation Modelling (SEM) method. The findings revealed a significant direct relationship between the website's design attractiveness, e-commerce marketplace reputation, and perceived ease of transaction with the customer's perceived value and between perceived value and the purchase decision. This study also found mediation effects of perceived value on the relationships between website design attractiveness and e-commerce marketplace reputation on online purchase decisions. Considering the importance of website design attractiveness, e-commerce marketplace reputation, perceived ease of transaction on customer-perceived value, and the role of customer-perceived value on online purchase decisions, this study recommends companies to strengthen their marketing strategies related to those three predictors of customer-perceived value. A good perceived value is expected to increase customers' online purchasing probability.